Solidaritas kesukuan dalam Pemilihan Wali Nagari - Fini Maitalia; Hasrul Hasrul; Susi Fitria Dewi; Cici Nur Azizah (Journal of Education, Cultural and Politics, 2026)
The election of a Wali Nagari is a form of local democratic practice that provides opportunities for the community to choose leaders based on the aspirations and needs of the nagari. However, in practice, political behavior is influenced not only by rational considerations but also by social and cultural factors that develop within the community, one of which is ethnic solidarity. This study aims to describe the forms of ethnic solidarity and analyze the factors influencing ethnic solidarity in the Wali Nagari Election in Nagari Siguntur Tua, Koto XI Tarusan District, Pesisir Selatan Regency. This research employed a qualitative approach using a descriptive method. The informants consisted of traditional leaders, community leaders, election committee members, and community members involved in the Wali Nagari election process. Data were collected through interviews, observations, and documentation and were analyzed using the Miles and Huberman interactive model, which includes data reduction, data display, and conclusion drawing. The findings reveal that ethnic solidarity in the Wali Nagari election is reflected in four main aspects: collective consciousness, a sense of togetherness, cooperation, and trust. Furthermore, the factors influencing ethnic solidarity include pride in one's ethnic group, group solidarity, and self-identification as a member of a particular ethnic group. The study concludes that ethnic ties continue to play a significant role in shaping community political behavior and strengthening social bonds within the society of Nagari Siguntur Tua.